Influences of the Menstrual Phase on Cortisol Response to Stress in Nicotine Dependent Women: A Preliminary Examination. Issue 5 (10th April 2018) - Nakajima, Motohiro; Allen, Sharon; al'Absi, Mustafa
Abstract: Introduction: Evidence indicates that menstrual cycle phase plays a role in smoking withdrawal symptoms and craving. Stress increases these symptoms. Whether the stress regulatory mechanism is associated with menstrual phase and withdrawal symptoms is not well understood. Methods: Thirty-seven female smokers and 16 female nonsmokers were asked to complete a laboratory session. In each group, approximately half of the participants were tested when they were in the follicular phase and the other half was tested in the luteal phase. The session included resting baseline, stress, and recovery periods. Saliva samples for the measurement of cortisol and subjective measures of craving and withdrawal symptoms were collected at the end of each period. Results: A series of repeated measures analysis of covariance found a significant smoking group × menstrual phase × sampling time interaction in cortisol levels ( p < .05). Follow-up analyses indicated a reduced cortisol stress response in the luteal group relative to the follicular group in smokers ( p < .02). This difference was not found in nonsmokers. Conclusions: Menstrual cycle phase is related to hormonal stress response and smoking withdrawal symptomatology. Implications: We show influences of the menstrual cycle phase on stress response among smokers. This is demonstrated by a reduced cortisol response to stress in the luteal group relative to the follicular group among smokers. This menstrual phase difference was not found in nonsmokers.